A comparative study of the mechanical properties and failure behavior of carbon fiber/epoxy and carbon fiber/polyamide 6 unidirectional composites. (15th January 2017) - Ma, Yan; Ueda, Masahito; Yokozeki, Tomohiro; Sugahara, Toshi; Yang, Yuqiu; Hamada, Hiroyuki
Abstract: Two types of unidirectional carbon fiber reinforced plastic were fabricated using identical carbon fibers but different matrix systems. Thermoplastic polyamide 6 and thermosetting epoxy were used as matrices. A large number of on-axis tensile tests of unidirectional carbon fiber reinforced polyamide 6 (CF/PA6) and the unidirectional carbon fiber reinforced epoxy (CF/Epoxy) laminates were performed. Mechanical properties and failure behaviors are discussed based on fiber distribution, impregnation conditions and interfacial shear strength. Tensile strengths were predicted by means of a modified global load sharing model and compared with experimental results. Step-by-step tensile tests revealed the fracture process of 0-degree unidirectional CF/PA6 laminates.